An overview: recent development of semiconductor/graphene nanocomposites for photodegradation of phenol and phenolic compounds in aqueous solution - Reyhaneh Kaveh (Journal of Asian Ceramic Societies, 2021)
The development of graphene-based nanocomposites is currently the issue of enormous research interest. Recent advancements have exhibited that semiconductor/graphene nanocomposites can be purposed as a promising new category of catalysts for the heterogeneous photocatalytic treatment of wastewaters. Since semiconductor/graphene nanocomposites have been found efficient in degradation of organic pollutants, photodegradation of phenol and phenolic compounds as hazardous contaminants in aqueous solution has been most widely investigated by these aforementioned nanocomposites. In the present review, after introduction on the properties and the different synthesis methods of semiconductor/graphene nanocomposites, we will discuss the application of these nanocomposites, in fields of photodegradation of phenol and phenolic compounds in aqueous solution.